A Compact Dual-Band Rectenna for GSM900 and GSM1800 Energy Harvesting. (9th July 2018) - Zeng, Miaowang; Li, Zihong; Andrenko, Andrey S.; Zeng, Yanhan; Tan, Hong-Zhou
Abstract : This paper presents a compact dual-band rectenna for GSM900 and GSM1800 energy harvesting. The monopole antenna consists of a longer bent Koch fractal element for GSM900 band and a shorter radiation element for GSM1800. The rectifier is composed of a multisection dual-band matching network, two rectifying branches, and filter networks. Measured peak efficiency of the proposed rectenna is 62% at 0.88 GHz 15.9 μ W/cm 2 and 50% at 1.85 GHz 19.1 μ W/cm 2, respectively. When the rectenna is 25 m away from a cellular base station, measurement result shows that the harvested power is able to power a batteryless LCD watch and achieve 1.275 V output voltage. The proposed rectenna is compact, efficient, low cost, and easy to fabricate, and it is suitable for RF energy harvesting and various wireless communication scenarios.